Monitoring Pergerakan Lereng Disposal dengan Total Station di Pit PT Fajar Sakti Prima, Kalimantan Timur - Elsa Amanda Putri; Tommy Trides; Shalaho Dina Devy; Revia Oktaviani; Albertus Juvensius Pontus (International Forum of Researchers and Lecturers, 2025)
Slope failure can occur even though slope design and reinforcement have been carried out. However, before it completely collapses, there are often signs from the slope. These signs should be carefully observed through slope monitoring or surveillance activities to provide advance warnings regarding the development of slope instability, allowing mitigation measures to be implemented to reduce or avoid the impacts of instability, as well as to predict the timing of landslides using Inverse Velocity. This study was conducted at the PIT of PT Fajar Sakti Prima in East Kalimantan Province. Observations were carried out over 39 days to obtain deformation behavior, velocity values for mitigation actions, and inverse velocity values to predict the timing of landslides. In this observation, the deformation behavior values at PM 01, PM 02, and PM 03 were initially linear, then exhibited progressive behavior on November 7-8, 2024. The predicted landslide timing from this observation was November 20-21, 2024. Based on velocity values correlated with the TARP, critical categories were obtained at 7.40 - 9.86 cm/day and very critical at >26.17 cm/day